The Contribution of the Tourism Sector to Palangka Raya City's Original Revenue - Santya G. Sianturi (Journal Magister Ilmu Ekonomi Universtas Palangka Raya : GROWTH, 2020)
ABSTRACT This study aims to determine the contribution of the tourism sector to the local revenue of the city of Palangka Raya. Collecting data with quantitative research. The types and sources of data used in this study are secondary data. The data was taken from the BPS and the Office of Youth, Sports, Culture, and Tourism of the City of Palangka Raya. The data analysis method used in this research is the analysis of Trend and Multiple Linear Regression. From the results of the trend test, it is concluded that the development of the tourism sector contribution has an effect on the Palangka Raya Regional Original Income and fluctuates or fluctuates. The results of multiple linear regression research explain that the variable number of tourism objects has no significant effect on the local revenue of the city of Palangka Raya, the variable number of tourists has a positive and significant effect on the original income of the city of Palangka Raya, and the variable number of hotel occupancy has a significant effect on the original income of the city of Palangka Raya.